Improving adolescent HPV vaccination in a randomized controlled cluster trial using the 4 Pillars™ practice Transformation Program. Issue 1 (3rd January 2017) - Zimmerman, Richard K.; Moehling, Krissy K.; Lin, Chyongchiou J.; Zhang, Song; Raviotta, Jonathan M.; Reis, Evelyn C.; Humiston, Sharon G.; Nowalk, Mary Patricia
Abstract: Objective: Uptake of meningococcal vaccine (MCV) and tetanus, diphtheria and pertussis (Tdap) vaccine among adolescents has approached Healthy People 2020 goals, but human papillomavirus (HPV) vaccination has not. This study evaluated an intervention using the 4 Pillars™ Practice Transformation Program to increase HPV, MCV and Tdap uptake among adolescents in primary care practices. Methods: Practices with at least 50 patients 11–17 years old with estimated vaccination rates less than national goals, were assigned to intervention (n = 11) and control (n = 11) groups in a randomized controlled cluster trial; 9 intervention and 11 control sites completed the study. The baseline and active study periods were 7/1/2013–6/30/2014 and 7/1/2014–3/31/2015, respectively. Vaccination and demographic data for patients who had a visit in both study periods were derived from de-identified EMR extractions. Primary outcomes were vaccination rates and percentage point (PP) changes. Data were analyzed in 2015–16. Results: Among the cohort of 10, 861 adolescent patients, 38% were 11–13 years old; 50% were female; 18% were non-white; and 64% were commercially insured. Average baseline HPV initiation rates were 52.5% for intervention and 61.8% for control groups. After 9 months, the intervention sites increased HPV initiation 10.2 PP compared with 7.3 PP in control sites ( P < 0.001); HPV series completion rates did not differ between groups. Implementation of >10 strategies to improve rates significantly increased the likelihood of HPV series initiation (OR = 2.06, 95% CI = 1.43, 2.96). Conclusions: Using >10 strategies from the 4 Pillars™ Practice Transformation Program is effective for increasing HPV series initiation among adolescents. Clinical trial registry number:NCT02165722 .